Factor the expression. x2 14x 45

Question

Asked 11/27/2014 8:36:55 AM

Updated 11/27/2014 9:40:43 PM

2 Answers/Comments

Flagged by janezeshun [11/27/2014 9:40:09 PM]

s

Question

Asked 11/27/2014 8:36:55 AM

Updated 11/27/2014 9:40:43 PM

2 Answers/Comments

Flagged by janezeshun [11/27/2014 9:40:09 PM]

Rating

5

x^2 - 8x + 12

= x*x - 2x - 6x + (-2)*(-6)

= (x - 2)(x - 6)

= x*x - 2x - 6x + (-2)*(-6)

= (x - 2)(x - 6)

Added 11/27/2014 9:40:03 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/27/2014 9:46:00 PM]

5

x^2 - 145x + 144

= x*x - x - 144x + (-1)*(-144)

= (x - 1)(x - 144)

= x*x - x - 144x + (-1)*(-144)

= (x - 1)(x - 144)

Added 11/27/2014 9:40:43 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/27/2014 9:46:45 PM]

-7w^3 + 6w^2 - 9w - 21w^2 + 18w - 27 **Weegy:** -7w^3 + 6w^2 - 9w - 21w^2 + 18w-27
= (-7w^3) + (6w^2 + -21w^2) + (-9w + 18w) + (-27)
= -7w^3 - 15w^2 + 9w - 27 (More)

Question

Expert Answered

Updated 11/28/2014 1:56:52 AM

0 Answers/Comments

Select the product of (-6x7y)(x3y5)

Question

Not Answered

Updated 11/24/2014 6:08:25 AM

1 Answer/Comment

(-6x^7y)(x^3y^5)

= -6x^7*x^3*y^5*y

= -6x^10y^6

= -6x^7*x^3*y^5*y

= -6x^10y^6

Added 11/24/2014 6:08:25 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/28/2014 1:57:22 AM], Rated good by andrewpallarca

Select the product of (5x - 4)(5x + 9).
25x2 - 25x - 36
50x - 36
25x2 + 25x - 36
10x + 5 **Weegy:** (5x + 1)? **User:** Select the product of (5x - 4)(5x + 9).
a. 25x2 - 25x - 36
b. 50x - 36
c. 25x2 + 25x - 36
d. 10x + 5 **Weegy:** (5x + 1)? **User:** (x + 4)3 (More)

Question

Updated 11/23/2014 11:37:33 PM

2 Answers/Comments

(5x - 4)(5x + 9)

= 5x*5x - 4*5x + 5x*9 - 4*9

= 25x^2 - 20x + 45x - 36

= 25x^2 + 25x - 36

= 5x*5x - 4*5x + 5x*9 - 4*9

= 25x^2 - 20x + 45x - 36

= 25x^2 + 25x - 36

Added 11/23/2014 11:34:57 PM

This answer has been confirmed as correct and helpful.

Rated good by andrewpallarca, Confirmed by andrewpallarca [11/24/2014 2:10:54 AM]

(x + 4)^3

= (x + 4)(x + 4)(x + 4)

= (x^2 + 8x + 16)(x + 4)

= x^3 + 8x^2 + 16x + 4x^2 + 32x + 64

= x^3 + 12x^2 + 48x + 64

= (x + 4)(x + 4)(x + 4)

= (x^2 + 8x + 16)(x + 4)

= x^3 + 8x^2 + 16x + 4x^2 + 32x + 64

= x^3 + 12x^2 + 48x + 64

Added 11/23/2014 11:37:33 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/24/2014 2:11:40 AM], Rated good by andrewpallarca

the product of (3x - 9)(3x - 9).

Question

Not Answered

Updated 11/24/2014 6:52:32 AM

1 Answer/Comment

(3x - 9)(3x - 9)

= 3x*3x - 9*3x - 3x*9 + (-9)*(-9)

= 9x^2 - 27x - 27x + 81

= 9x^2 - 54x + 81

= 3x*3x - 9*3x - 3x*9 + (-9)*(-9)

= 9x^2 - 27x - 27x + 81

= 9x^2 - 54x + 81

Added 11/23/2014 11:33:22 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/24/2014 6:52:27 AM]

simplify 64w^2 -64w-16w+16

Question

Updated 11/23/2014 6:08:26 PM

1 Answer/Comment

64w^2 - 64w -16w+16

= 64w^2 - 80w + 16

= 16(42^2 - 5w + 1)

= 16(4w - 1)(w - 1)

= 64w^2 - 80w + 16

= 16(42^2 - 5w + 1)

= 16(4w - 1)(w - 1)

Added 11/23/2014 6:08:26 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/24/2014 5:43:17 AM]

34,466,103

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 813 [Total 6686] Ratings 19 Comments 623 Invitations 0 Offline

There are no comments.